2014
DOI: 10.3109/09540261.2014.924097
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for parenthood programme: Experiences from southern India

Abstract: Parenting skills are critically important to ensure that children are brought up in a safe environment. Recent evidence shows that studies of parenting skills are still at a preliminary stage in low- and middle-income countries. These need to involve family practitioners and religious groups who often play a major role in preparing young people in India. There are organized programmes available in the country for Christian adults to prepare themselves for marriage and family life through various church initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…(15,31) In spite of this situation, women in the study by Ho and Holroyd (8) considered that the prenatal period is the ideal to get prepare on matters related to maternity. McVeigh (30) proposes that anticipated preparation for maternity is required in its own social environment and that society needs to actively prepare its youth for one of the most demanding social roles, as shown by Thomas and Bhugra (32) who identified that young people recognized a need to have programs for preparation for maternity to learn to solve problems on this issue before assuming their role as parents.…”
Section: Related Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…(15,31) In spite of this situation, women in the study by Ho and Holroyd (8) considered that the prenatal period is the ideal to get prepare on matters related to maternity. McVeigh (30) proposes that anticipated preparation for maternity is required in its own social environment and that society needs to actively prepare its youth for one of the most demanding social roles, as shown by Thomas and Bhugra (32) who identified that young people recognized a need to have programs for preparation for maternity to learn to solve problems on this issue before assuming their role as parents.…”
Section: Related Conceptsmentioning
confidence: 99%
“…(32) Additionally, through the availability of financial resources that favor the acquisition of care giving elements and the adaptation of spaces (9) and the preparation for labor and delivery. (22) In other conceptual developments, preparation for maternity has other legal, spiritual, and historical dimensions; (9) but is placed within a context reduced to the presence of a relationship between a man and a woman, with a planned pregnancy and extended to the child's first year of life.…”
Section: Year Empirical Reference Measurement Scalementioning
confidence: 99%